Has the 'Fast-Track' referral system affected the route of presentation and/or clinical outcomes in patients with colorectal cancer?. Issue 1 (December 2016) - Thornton, Luke; Reader, Harriet; Stojkovic, Stevan; Allgar, Victoria; Woodcock, Nick
Abstract Background The aim of this study is to determine whether the 'Fast-Track' referral system has changed the route by which patients present with colorectal cancer (CRC) and whether the route of presentation has any effect on clinical outcome. Methods A retrospective cohort study of patients diagnosed with CRC under the care of two consultant colorectal surgeons between April 2006 and December 2012. The route by which patients presented was categorised as Fast-Track (FT), non-Fast-Track (non-FT) or acute. Outcome variables were operative intent, disease stage and 2- and 5-year survival. Results A total of 558 patients were identified. One hundred ninety-seven patients (35.3 %) were referred as FT, 108 (19.4 %) presented acutely and 253 patients (45.3 %) presented via other routes (non-FT). Over the study period, the route of presentation did not change significantly (P = 0.135). There was no significant difference between FT and non-FT groups in terms of the proportion of patients undergoing potentially curative surgery (70.6 vs 74.3 %, P = 0.092) or with node-negative disease (48.2 vs 52.2 %, P = 0.796) nor was there any difference in 2-year or 5-year survival (74.1 vs 73.9 %, P = 0.837 and 52.3 vs 53.8 %, P = 0.889, respectively). Patients who presented acutely were less likely to undergo curative resection, had more advanced disease and had worse 2- and 5-year survival. Conclusions The Fast-Track referral system has not affected the route by which patients present with CRC nor has it had any effect on clinical outcomes. Alternative strategies are required if the desired improvement in outcomes is to be achieved.